2017
DOI: 10.1103/physrevlett.118.230401
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement and Nonlocality in Infinite 1D Systems

Abstract: We consider the problem of detecting entanglement and nonlocality in one-dimensional (1D) infinite, translation-invariant (TI) systems when just near-neighbor information is available. This issue is deeper than one might think a priori, since, as we show, there exist instances of local separable states (classical boxes) which only admit entangled (non-classical) TI extensions. We provide a simple characterization of the set of local states of multi-separable TI spin chains and construct a family of linear witn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 31 publications
(2 reference statements)
1
51
0
Order By: Relevance
“…This conundrum is at the essence of the TI MARGINAL problem , where a number of probability distributions of finitely-many variables are provided and the task is to certify if they correspond to the marginals of a TI system. MARGINAL arises naturally at the intersection of quantum information science and condensed matter physics, when we try to determine whether the dynamical structure factors of a large spin system are compatible with an underlying Bell local quantum state [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conundrum is at the essence of the TI MARGINAL problem , where a number of probability distributions of finitely-many variables are provided and the task is to certify if they correspond to the marginals of a TI system. MARGINAL arises naturally at the intersection of quantum information science and condensed matter physics, when we try to determine whether the dynamical structure factors of a large spin system are compatible with an underlying Bell local quantum state [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the desire of understanding the nature of quantum non-locality in 2D materials [ 2 ], in this paper we will considerably advance the above fundamental questions. We will show that, in scenarios where the random variables take a small number d of possible values, the MARGINAL problem for nearest-neighbour (for d = 2, 3) and next-to-nearest neighbour distributions (for d = 2) is exactly solvable.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial structure of entanglement, on the other hand, is rather revealed through the bipartite Schmidt decomposition, which captures entanglement at a many-body level. Developing further conceptual and technical tools to investigate non-local correlations in spatially structured many-body states is an important challenge for ongoing studies [24].…”
mentioning
confidence: 99%
“…For this reason, the implications of nonlocal correlations in systems consisting of a very large number of parties has been mostly lacking, despite remarkable results have been obtained throughout the years [27][28][29][30][31][32][33][34][35][36][37]. Interestingly, recent theoretical advances developed in the context of few-body Bell inequalities [38][39][40][41][42][43][44][45][46] have allowed for simple ways to detect these correlations in many-body systems. On the one hand, it has been shown that many-body observables such as the energy of the system could signal the presence of Bell correlations in the system [42].…”
Section: Introductionmentioning
confidence: 99%